Relative Oral Bioavailability of an Abuse-deterrent, Extended-release Formulation of Morphine Versus Extended-release Morphine: A 2-period, Single-dose, Randomized Crossover Study in Healthy Subjects - Kinzler, Eric R.; Pantaleon, Carmela; Aigner, Stefan (Clinical therapeutics, 2018)
Morphine ARER is a novel oral, abuse-deterrent, extended-release (ER) formulation of morphine sulfate with physical and chemical properties that deter misuse and abuse by nonoral routes of administration. Here we evaluate the relative bioavailability of morphine ARER and extended-release morphine. This single-dose, 2-treatment, 2-period, 2-sequence, randomized crossover study in healthy adult subjects compared the relative bioavailability of morphine ARER 100 mg to that of ER morphine 100 mg in the fasted condition. At 12 and 1.5 hours before dosing and 12 hours after dosing, all subjects received a 50-mg oral naltrexone tablet to minimize opioid-related side effects. Pharmacokinetic parameters including the AUC0–t, AUC0–∞, and Cmax of morphine and its metabolite morphine-6-glucuronide (M6G) were determined at various times up to 48 hours postdose. The bioequivalence of morphine ARER and ER morphine was determined using an ANOVA of the least-squares mean values of morphine and M6G bioavailability. Forty-nine subjects completed the study. Both morphine ARER and ER morphine exhibited peak plasma morphine and M6G concentrations of ∼30 ng/mL and ∼200 ng/mL, respectively, at 3 hours postdose. The 90% CIs of the ln-transformed values of morphine AUC0–t, AUC0–∞, and Cmax were within the 80% to 125% range for bioequivalence. M6G values also indicated bioequivalence of morphine ARER and ER morphine. The most common adverse events were nausea and somnolence. These data show that, in these subjects, morphine ARER was bioequivalent to ER morphine, a treatment for pain with well-established efficacy and safety profiles.